Restorative Justice and Post-Genocide Reconciliation: Ethical Implications and Community Healing in Rwanda - Jonas Musengimana (Journal of Ethics in Higher Education)
This paper explores the role of restorative justice in post-genocide reconciliation in Rwanda, focusing on its ethical implications and impact on community healing. Following the 1994 genocide against the Tutsi, Rwanda faced the challenge of addressing survivors' trauma, fostering national unity, and reconciling a divided society. Key initiatives, including the Gacaca court system, emphasized dialogue, accountability, and forgiveness to promote healing. Using restorative justice and social reconstruction theories as its conceptual frameworks, this study examines how restorative justice fosters trust, dignity, and relationship restoration, while addressing ethical challenges. Also, through a desk review of existing literature, reports, and case studies, this study synthesizes key findings on the effectiveness of restorative justice.